Answer:
# The solution x = -5
# The solution is x = 1
# The solution is x = 6.4
# The solution is x = 4
# The solution is 1.7427
# The solution is 0.190757
Explanation:
* Lets revise some rules of the exponents and the logarithmic equation
# Exponent rules:
1- b^m × b^n = b^(m + n) ⇒ in multiplication if they have same base
we add the power
2- b^m ÷ b^n = b^(m – n) ⇒ in division if they have same base we
subtract the power
3- (b^m)^n = b^(mn) ⇒ if we have power over power we multiply
them
4- a^m × b^m = (ab)^m ⇒ if we multiply different bases with same
power then we multiply them ad put over the answer the power
5- b^(-m) = 1/(b^m) (for all nonzero real numbers b) ⇒ If we have
negative power we reciprocal the base to get positive power
6- If a^m = a^n , then m = n ⇒ equal bases get equal powers
7- If a^m = b^m , then a = b or m = 0
# Logarithmic rules:
1-
![log_(a)b=n-----a^(n)=b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r0yovdi7dheah80q4zv3vpl6fb9nb152ur.png)
2-
![loga_(1)=0---log_(a)a=1---ln(e)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kdww77cgcnjl8fdjqpekjte44k6zyx8neh.png)
3-
![log_(a)q+log_(a)p=log_(a)qp](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i5jndusfkhe0oq57kskqwwml6tzj7ap3ix.png)
4-
![log_(a)q-log_(a)p=log_(a)(q)/(p)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fg16ljkim2pjaob8c5ikef0wlu8s8sjovq.png)
5-
![log_(a)q^(n)=nlog_(a)q](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e4jyvegh6kzvl6tlf51vqm1ovw8w068zci.png)
* Now lets solve the problems
#
![3^(x+1)=9^(x+3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hs8n83yai26c7zju3s097rv4h94kz1bka7.png)
- Change the base 9 to 3²
∴
![9^(x+3)=3^(2(x+3))=3^(2x+6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pvz66pn2m3wke755x3tj3lc7en5ydhtcyj.png)
∴
![3^(x+1)=3^(2x+6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/muxnqbmxqw4qvv8ceciampgioa9tyms4s8.png)
- Same bases have equal powers
∴ x + 1 = 2x + 6 ⇒ subtract x and 6 from both sides
∴ 1 - 6 = 2x - x
∴ -5 = x
* The solution x = -5
# ㏒(9x - 2) = ㏒(4x + 3)
- If ㏒(a) = ㏒(b), then a = b
∴ 9x - 2 = 4x + 3 ⇒ subtract 4x from both sides and add 2 to both sides
∴ 5x = 5 ⇒ divide both sides by 5
∴ x = 1
* The solution is x = 1
#
![log_(6)(5x+4)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kmkwk4nuhfx6y89caqmdes3t00mcjyu2ls.png)
- Use the 1st rule in the logarithmic equation
∴ 6² = 5x + 4
∴ 36 = 5x + 4 ⇒ subtract 4 from both sides
∴ 32 = 5x ⇒ divide both sides by 5
∴ 6.4 = x
* The solution is x = 6.4
#
![log_(2)x+log_(2)(x-3)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hcs6ynz0x5fsbjq09bajxnipp2xgxyl3du.png)
- Use the rule 3 in the logarithmic equation
∴
![log_(2)x(x-3)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k56snil208ep9us91980ka681xyf02l6zg.png)
- Use the 1st rule in the logarithmic equation
∴ 2² = x(x - 3) ⇒ simplify
∴ 4 = x² - 3x ⇒ subtract 4 from both sides
∴ x² - 3x - 4 = 0 ⇒ factorize it into two brackets
∴ (x - 4)(x + 1) = 0 ⇒ equate each bract by 0
∴ x - 4 = 0 ⇒ add 4 to both sides
∴ x = 4
OR
∵ x + 1 = 0 ⇒ subtract 1 from both sides
∴ x = -1
- We will reject this answer because when we substitute the value
of x in the given equation we will find
and this
value is undefined, there is no logarithm for negative number
* The solution is x = 4
#
![log_(4)11.2=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2cn7kjodtptq6uw01ayjmrf7g163pjiv6g.png)
- You can use the calculator directly to find x
∴ x = 1.7427
* The solution is 1.7427
#
⇒ divide the both sides by 2
∴
![e^(8x)=4.6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ryofbe174qtyl9uauyxlxkfnqbz6afdbq1.png)
- Insert ln for both sides
∴
![lne^(8x)=ln(4.6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/infvwv6r4qz9nqf9d39ozgeqnaj2zn4e84.png)
- Use the rule
⇒ ln(e) = 1
∴ 8x = ln(4.6) ⇒ divide both sides by 8
∴ x = ln(4.6)/8 = 0.190757
* The solution is 0.190757